THE ARTISTIC INTERPRETATION OF EDUCATION, LEARNING AND MORAL ISSUES (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article presents a scholarly analysis of the artistic interpretation of education, learning and moral issues in Uzbek literature. Based on historical and contemporary literary sources, the didactic, aesthetic and philosophical representation of these topics is revealed. Relying on the works of M.Khajiyeva, A.Avloni, S. Dolimov and U.Dolimov, the formation of moral ideas through artistic imagery, their integration with scientific thinking, and the role of spiritual education in societal development are explained.